Power Season 5 - Sikora, Joe; Johnson, Shane; Rainey Jr., Michael; Anthony, La La; Sadler, William; Tate, Larenz; Hardwick, Omari, 1974-; Naughton, Naturi, 1984-; Loren, Lela, 1980-; Akinosho, Rotimi; 50 Cent, (Musician); Ferrara, Jerry, 1979-; et al. ([United States] : Lionsgate, 2019)
As Ghost mourns his daughter's death, he searches for vengeance and throws himself into his work, reaching new professional heights. But his quest for blood threatens to dismantle his legitimate legacy. He's blind to new enemies, and as the feds grow closer to unmasking his true identity. Ghost must remain vigilant toward those wanting to take him down for his past criminal enterprises.
05/14/2019
Omari Hardwick, Naturi Naughton, Joseph Sikora, Shane Johnson, Lela Loren, Rotimi, Michael Rainey Jr., 50 Cent, La La Anthony, Jerry Ferrara, William Sadler, Sung Kang, Larenz Tate, Matt Cedeno.
MWT rating: NR.
DVD.
English, Spanish audio; Spanish subtitles.
English subtitles for the deaf and hard of hearing.
Keywords: Television series